A inclusão digital para crianças e adolescentes: um estudo de caso da empresa Jedais Tec no município de Benjamin Constant-AM - Pereira, Rogério Mendonça (Brasil, 2024)
Faced with a scenario where digitalisation is essential, this study looks at access to and use of digital resources by pupils and the preparation of educators in integrating these technologies. The general objective was to explore how Jedais Tec's initiatives in technological education influence the education of children and young people in Benjamin Constant-AM. The specific objectives were to analyse how the Jedais Tec School manages its educational activities, assessing effectiveness and youth engagement; to investigate the compatibility between the Jedais Tec business model and local educational and technological demands; and to assess how students, parents and the community see the value of the computer school, highlighting elements of success or challenge. Technologies are increasingly important in the lives of students at different levels of education. With this in mind, this study seeks to understand digital inclusion in the Alto Solimões region. Using a qualitative and quantitative approach, interviews were conducted using Google Forms, highlighting the role of educational technologies in promoting engagement and developing skills. The results point to significant access to technology, albeit with challenges such as infrastructure and teacher training. The results indicate that, despite the barriers, there is a positive impact of digital inclusion on student motivation and learning, highlighting the need for public policies and private initiatives to strengthen the technological structure and professional training. This study reinforces the importance of administration in facilitating digital inclusion, which is essential for the socio-economic and educational development of the region.